2018
DOI: 10.14738/assrj.56.4694
|View full text |Cite
|
Sign up to set email alerts
|

Hiv Testing and Counselling Among the Youth of Ghana: The Case of Tarkwa-Nsuaem and Fanteakwa District

Abstract: This study was conducted to examine the factors that contribute to the utilization of HIV Testing and Counselling (HTC) among the youth in Ghana focusing on Fanteakwa District and Tarkwa-Nsuaem Municipality in light of the Health Belief Model. The study involved 424 youths between the ages of 15-24. The quantitative approach was used in the study. Multi-stage sampling technique was adopted for the study involving the purposive sampling which was used to select the two districts and then the simple random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The uptake of HTC was low (29.2%). HTC uptake in the present study is similar to the findings reported in previous studies conducted in Tarkwa-Nsuaem and Fanteakwa Districts, Ghana [ 37 ], the Hohoe Municipality, Ghana [ 18 ], Kenya [ 28 ] and Tanzania [ 20 ]. However, it is lower compared to findings from previous studies conducted in sub-Saharan Africa [ 22 ], Ethiopia [ 10 ], Ho Ghana [ 17 ], Accra Ghana [ 15 ], and Kumasi Ghana [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The uptake of HTC was low (29.2%). HTC uptake in the present study is similar to the findings reported in previous studies conducted in Tarkwa-Nsuaem and Fanteakwa Districts, Ghana [ 37 ], the Hohoe Municipality, Ghana [ 18 ], Kenya [ 28 ] and Tanzania [ 20 ]. However, it is lower compared to findings from previous studies conducted in sub-Saharan Africa [ 22 ], Ethiopia [ 10 ], Ho Ghana [ 17 ], Accra Ghana [ 15 ], and Kumasi Ghana [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The plausible justification of the observed utilisation is that the facilities offering the HTC services may not be user-friendly, thereby leading to distrust between users and health workers. Also, deep-rooted societal perception of sexual promiscuity often associated with youth who utilise HTC services could hinder their ability to utilise these services [ 37 ]. The siting of the facilities coupled with some misconceptions about HTC could have also influenced the low HTC uptake.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Others studies conducted in public, as well as private universities in Accra and Kumasi (Ghana), reached the same conclusion regarding the low HTC uptake in Ghana. 15,24 Knowing routes of HIV transmission 15 , age, gender, place of residence, perceived susceptibility to HIV, 25 having multiple sexual partners, practising unprotected sex and being aware of HTC services 26 are associated with a high HTC uptake. Inversely fear, being uninformed about HTC, and low HIV risk perception are associated with not getting tested.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies conducted in Ghana reveal that only 25 per cent had utilized HTC [7,8]. Early diagnosis of youth with HIV/AIDS can take place only with participation in HTC, which is affected by factors such as fear for HIV test, lack of trust for health personnel (confidentiality), unavailability of ART, stigmatization, inadequate HTC centres, cultural sensitivity and religious believes [9,10].…”
Section: Introductionmentioning
confidence: 99%